The Effect Of The Utilization Of Digital Marketing On The Competitiveness Of Micro, Small, and Medium Enterprises (MSMEs) In Bone District - Wisudawan, Edwin; Hanawi Haris; Aris Baharuddin; Syarifuddin (Business Research and Administration Innovation, 2024)
This study aims to determine how much influence the use of Digital Marketing has on the competitiveness of SMEs in Bone Regency. This study uses a quantitative descriptive type of research with data collection techniques through observation and questionnaires. The sample used in this study was 100 respondents. The data of this study were obtained from the results of data processing using the SPSS 25 application which consisted of validity and reliability tests, descriptive data analysis techniques and inferential analysis. The results of this study indicate that the variables of Digital Marketing Utilization and MSME Competitiveness in Bone Regency have a significant influence. This is evidenced by the results of a simple linear regression test and a correlation coefficient test of 0.600, which means that the relationship between Digital Marketing Utilization and MSME Competitiveness is good/strong. And the Coefficient of Determination Test R^2 was obtained at 0.360, which means that the influence of Digital Marketing Utilization on MSME Competitiveness in Bone Regency obtained a value of 36.0%, while the remaining 64.0% was influenced by other factors.